Studi Komparatif mengenai Kreativitas antara Siswa SD RegulerâXâ dengan SD bertaraf Internasional âYâ yang Berusia 10-12 tahun di Bandung (Studi Kasus di Balai Besar Keramik) - Octavia, Yolla; Victoriana, Evany; Adelina, Ira (Zenit, 2013)
This research is to find description of comparison of creativity on 10-12 years old students between regular primary school âXâ and intenational primary school âYâ in Bandung. This research uses comparative method. Purposive sampling is used for  selecting samples. The samples in this research consist of 68 students of regular primary school âXâ and 34  students of international primary school âYâ. The researcher uses Tes Kreativitas Figural (TKF) by Munandar as the instrument. The data is statistically analyzed in the form of means comparison using independent sample T-test. Based on the data analysis, the result shows, the significancy is 0,964 (two tails) and α is 0,05. In other ways, it shows there is no significant differences of creativity between both of them. So, both of them have same creativity. The researcher suggests a further research to combine  the instrument by using  Tes Kreativitas Verbal (TKV) and Tes Kreativitas Figural (TKF). So, it can collect the data  more complete and accurate. And also, to compare another school that has different curriculum that aims to improve student‘s creativity.Keywords : creativity, students, primary school